1996
DOI: 10.5032/jae.1996.01056
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Plan for Agricultural Education: An Assessment in Pennsylvania

Abstract: Numerous changes have occurred in agricultural education in an attempt to revitalize and revolutionize the way we teach agriculture. In this regard, the strategic planning process directed educators to move programs toward a more holistic view of the teaching of agriculture. The findings in this study indicate that teachers in Pennsylvania want to develop a strategic plan for the state. Moreover, the teachers indicated there should be a greater alliance of academics and agricultural education. The findings pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Agricultural education has been struggling with strategic planning on the national level for many years (Eaton & Bruening, 1996;NRC, 1988;Pope, 1992). Recommendations resulting from national studies such as Understanding Agriculture: New Directions for Agricultural Education (NRC, 1988) have not met with success in terms of mobilizing the teacher educators to develop a response to the recommendations (Conroy, 1997).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Agricultural education has been struggling with strategic planning on the national level for many years (Eaton & Bruening, 1996;NRC, 1988;Pope, 1992). Recommendations resulting from national studies such as Understanding Agriculture: New Directions for Agricultural Education (NRC, 1988) have not met with success in terms of mobilizing the teacher educators to develop a response to the recommendations (Conroy, 1997).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Specifically, two research teams have studied strategic plans and public policy impacts. First, Eaton and Bruening (1996) (Conroy, 2000a), and found that stakeholders agreed that a science-based agricultural education program would improve the image of agricultural education if it remained community-based, invoked experiential learning, and stimulated leadership development (Dailey, Conroy, & Shelley-Tolbert, 2001). Further, Dailey et al found that the greatest challenges facing agricultural education today that were also identified by the NRC were: (a) making people aware of the importance of and new changes in agriculture; (b) recruiting and keeping students interested and involved in agriculture; and, (c) promoting agriculture and dispelling common misconceptions about agriculture.…”
Section: Introductionmentioning
confidence: 99%